Physical model test on soil slopes under the effect of bedrock fault dislocations - Yijie Song; Jianyi Zhang; Jianke Ma; Xiaobo Li; Haonan Zhang; Ruijie Hu (PLoS ONE, 2025)
Bedrock fault dislocations significantly influence the rupture instability of rock and soil slopes adjacent to fault zones. Understanding the dynamic processes, kinematic characteristics, and genesis mechanisms of landslides induced by strong seismic fault dislocations is crucial for advancing the theoretical framework of landslide studies. This paper presents a representative experiment simulating the emergence of seismic faults (internal rupture belts within the soil mass) at the shoulders and toes of slopes due to bedrock fault dislocations. Two failure modes were examined: soil mass rupture at the shoulders and the toe of the slope. The rupture at the shoulders was found to pose a greater threat to the stability of the soil slopes under intense fault dislocations. Furthermore, the genesis mechanisms and dynamic characteristics of sandy soil slopes destabilized by reverse fault dislocations can be categorized into three stages: Stage I, the gestation stage of slope soil mass rupture; Stage II, the development stage of the slope soil mass rupture zone; and Stage III, the stage of rupture-induced landslides. The study findings can be useful in slope stability analysis under bedrock dislocation conditions as well as for slope protection and management near fault zones. Both model tests and field cases of earthquake damage demonstrate a strong correlation between the location of the main fracture zone on the slope surface (at the slope shoulder and slope toe) and the displacement of the two walls of the bedrock fault.